2012
DOI: 10.1073/pnas.1120188109
|View full text |Cite
|
Sign up to set email alerts
|

Action potential propagation in transverse-axial tubular system is impaired in heart failure

Abstract: The plasma membrane of cardiac myocytes presents complex invaginations known as the transverse-axial tubular system (TATS). Despite TATS's crucial role in excitation-contraction coupling and morphological alterations found in pathological settings, TATS's electrical activity has never been directly investigated in remodeled tubular networks. Here we develop an ultrafast random access multiphoton microscope that, in combination with a customly synthesized voltage-sensitive dye, is used to simultaneously measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 36 publications
(41 reference statements)
9
123
0
Order By: Relevance
“…The Kâ€Č distribution highlights the presence of tubules experiencing an exceptionally low conductivity of the surrounding network. This finding is in line with previous observations where AP propagation failure across TATS was described in acutely detubulated cardiomyocytes (11).…”
Section: Tats Diffusion Propertiessupporting
confidence: 83%
See 4 more Smart Citations
“…The Kâ€Č distribution highlights the presence of tubules experiencing an exceptionally low conductivity of the surrounding network. This finding is in line with previous observations where AP propagation failure across TATS was described in acutely detubulated cardiomyocytes (11).…”
Section: Tats Diffusion Propertiessupporting
confidence: 83%
“…Ensuring a good electrical coupling of the TATS is essential for propagation of membrane depolarization from the surface to the core of the cell. Measurement of AP propagation in the TATS is a quite recent possibility, achieved by combining random access two-photon microscopy and voltage imaging (11,35). In line with the above considerations, this methodology revealed that the majority of T-tubules properly propagate the AP, even in diseased cardiomyocytes (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations